Christmas holiday triggers of myocardial infarction. (14th October 2021) - Olsson, A; Thoren, I; Mohammad, M; Rylance, R; Platonov, P; Sparv, D; Erlinge, D
Abstract: Background: Christmas holidays have been associated with the highest incidence of myocardial infarction (MI). We wanted to assess possible triggers of MI during Christmas. Method: A nationwide, retrospective postal survey with case-control design. All individuals suffering a MI during the Christmas holidays 2018 and 2019 in Sweden were identified through the SWEDEHEART registry and a control group matched in age and gender with chronic coronary syndrome who did not seek medical attention during Christmas, were asked for participation. Subjects completed a questionnaire asking them to rate 27 potential MI-triggers as having occurred more or less than usual. Results: A total of 189 patients suffering a MI on Christmas Eve, Christmas Day, or Boxing Day and 157 patients in control-group responded to the questionnaire, representing response rates of 66% and 62%, respectively. Patients with MI on Christmas experienced more stress (36.7% vs 20.9%, p=0.002), depression (20.9% vs 10.5%, p=0.024) and worry (25.9% vs 10.1%, p<0.001) compared to the control-group. The food and sweets-consumption were increased in both groups, but to a greater extent in the control-group (33.0% vs 49.7%, p=0.002 and 32.4% vs 43.3, p=0.031). There were no increases in quarrels, anger, economic worries or reduced compliance with medication. Conclusions: Patients suffering MI on Christmas holiday experienced higher levels of stress and emotional distress compared to patients with chronic coronary syndrome, possibly explaining the phenomenon of holiday heart attack. Understanding what factors increase the number of MI on Christmas may help reduce the excess number of MIs and cardiovascular burden. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Heart and Kund FoundationSwedish Scientific Research Council